FEMINISME DAN KESETARAAN GENDER PERSPEKTIF AL QUR’AN - Nuraini Habibah (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2022)
Feminism is a movement of women fighters who want equal rights and equal roles between men and women who are both God's creatures. History records that until now there are still many women who have not received their rights, and equality of roles between men and women has not been realized fairly. Muslim scholars and religious scholars consider feminism not a problem in Islam because in principle feminism has a close relationship with Islamic theology. Islam regulates the obligations and rights of men and women very fairly. Each has a function and role according to nature, there is no subordination between the two. This study aims to determine how Islam views the concept of feminism and gender equality. This study uses a qualitative descriptive method by taking data from various library sources related to the concept of feminism and gender equality from an Islamic perspective. The findings of this study are that men and women have equal rights and equal roles.